PENYULUHAN DAN SOSIALISASI SISTEM LAYANAN ”PORTAL EMAS” PADA MAHASISWA UNIVERSITAS PANCA MARGA - Supriyanto; Nurul Jannah Lailatul Fitria (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
Innovations in public sector services continue to vary and become more sophisticated. The government always tries to innovate in public sector services. As implemented by the Probolinggo City Government with the Portal Emas application. Online services through applications that include oral, written, and even direct action services. However, there are still many people who have not used the Portal Emas application. So that the community service team from 2019 students of the Public Administration Study Program, Faculty of Social and Political Sciences, Panca Marga University compiled a community service program with the theme of Extension and Socialization of the Probolinggo City " Portal Emas" Service System which was held for Panca Marga University students. The method used is counseling and online socialization with the stages of pre-activity, implementation of activities, and post-activity. In the implementation structure, the event consists of three parts, namely the delivery of material, directions for using the Portal Emas application and a question and answer session. The interactive pattern is applied from the beginning of implementation to involve all partners. Enthusiastic partners in every part of the activity. In the last stage, an evaluation is held which is conceptualized with a feedback system. The result of this service activity is that students gain knowledge and understanding related to materials, public sector services and methods of using the Portal Emas application. The output is in the form of an e-book that can be read by partners and the public. Service activities are important to disseminate material about public sector service innovation, the Portal Emas program and instructions for use to minimize the lack of information related to services and minimize errors in the practice of using the Portal Emas application.